Preparo e caracterização de blendas poliméricas de quitosana/poli(ácido acrílico) - Vieira, Paulo César Silva (Universidade Federal Rural do Semi-Árido, 2018)
Chitosan and acrylic poly acid are polymers that show great versatility and potential in pharmacological applications because their biocompatible and biodegradable properties. Some theses properties are atoxity, composed of fungistatic and bacteriostatic (to chitosan) and anionic feature (to PPA) which is appropriate for systems coverage of oral release. Once the work was started the characterization of commercial chitosan by conductometric titration to determine the degree of deacetylation and viscosimetry to obtain average molar mass of chitosan. The acrylic poly was obtained commercially in a manipulation pharmacy. This work aims to prepare and to distinguish biocompatible and biodegradable Chitosan blends and acrylic poly acid. A chitosan membrane was produced and altered with aqueous polyacrylic acid solution. Then one of the faces of the membrane was put in contact with PPA in room temperature and and at a temperature of 60 ° C. The chitozen membrane and acrylic poly acid are prepared at a room temperature and at 60 ° C. They were submitted to one characterization to gain mass in water, solid content and simulation of stomach transit. According about results obtained, it is possible to verify the membranes were threated with acrylic poly acid and which ones had satisfactory performance with useful characteristics for use in release technology controlled for drugs.
Monografia
Keywords: Blenda; Quitosana; Poli(ácido acrílico); CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA